The Construction of the Welfare State in Human Rights in Law Number 36 of 2009 concerning Health - Daisahbeny, Daisahbeny (Law Research Review Quarterly, 2023)
In the Preamble of the 1945 Constitution of the Republic of Indonesia (UUD 1945), it mandates that one of the objectives of establishing the Republic of Indonesia is to promote the general welfare and to educate the nation. This mandate implies an obligation to fulfill the needs of all citizens through a governance system that supports the creation of high-quality public services in order to meet the basic needs and civil rights of every citizen for public goods, public services, and administrative services. This is in line with the concept of a welfare state, which is the idea that the state is responsible for its citizens, ensuring their well-being through services, assistance, protection, and the prevention of social problems. Indonesia is one of the countries that adheres to this system by adopting a minimal welfare state model. One of the rights that the state must fulfill for its citizens is the right to access healthcare facilities, as outlined in Law Number 36 of 2009 concerning Health, which includes the obligation of every individual to respect the rights of others in their efforts to obtain a healthy environment, both physically, biologically, and socially. Every person is obligated to lead a healthy life to achieve, maintain, and improve their health to the highest possible level.